Concurrent bacterial liver abscess and mild encephalitis/encephalopathy with reversible splenial lesion in a patient with poorly controlled type 2 diabetes - Sekikawa, Naohiro; Hirai, Hiroyuki; Sugimoto, Kazuhiro; Kusano, Yoshiro (Diabetology international, 2023)
A 34-year-old man with poorly controlled type 2 diabetes was admitted to our hospital because of fever, headache, vomiting, and impaired consciousness. His hemoglobin A1c level was as high as 11.0%. Abdominal computed tomography revealed a bacterial liver abscess, while head magnetic resonance imaging simultaneously showed a high-signal lesion on diffusion-weighted imaging and a low-signal lesion on the apparent diffusion coefficient map of the splenium of the corpus callosum. No significant findings were detected in the cerebrospinal fluid. The latter findings led to a diagnosis of mild encephalitis/encephalopathy with reversible splenial lesions. His impaired consciousness resolved on Day 5 after treatment with ceftriaxone and metronidazole infusion and intensive insulin therapy; magnetic resonance imaging on Day 20 showed that the lesion in the splenium of the corpus callosum had disappeared. We propose that when a person with poorly controlled diabetes develops a bacterial infection and presents with impaired consciousness and headache, clinicians should consider the complications of mild encephalitis/encephalopathy with reversible splenial lesion.